The Effect of Green Intellectual Capital On Competitive Advantage With Corporate Social Responsibility as A Mediating - Arizqa Setiadi, Nanda; Saraswati, Aida; Dwi Astuti, Christina (Green Publisher Indonesia, 2022)
Study this aim for knowing the effect of green intellectual capital (green relational capital, green human capital, and green structural capital) on competitive advantage with corporate social responsibility as a mediator. Study this using primary data collected through questionnaire google forms help. The population in the study are employees who have involvement with the division of R&D, marketing, HR, and departments' protection working environment in the company manufacturing area of Jakarta, Bogor, Depok, Tangerang, and Bekasi (JABODETABEK). The amount of sample used is as much as 260 with the use convenience sampling method. The analytical tool used in research is SPSS. Result study with the use of analysis multiple linear regression show that : (1) Green human capital, green relational capital, and green structural capital have an effect positive significant on competitive advantage, (2) Corporate social responsibility, green relational capital, green human capital, and green structural capital have an effective positive significant to competitive advantage, (3) Corporate social responsibility can mediate the effect of green relational capital, green human capital and green structural capital on competitive advantage